Ethical Considerations in Software & Information Systems Engineering: The Case of a Local Hospital in Adamawa State of Nigeria - Ume, Arthur U. (Richtmann Publishing, 2012)
For more than a decade now, Nigeria has been witnessing a continuous improvement and boom in theapplication of Information and Communications Technology in all the vital sectors of her economy. Thereis an increasing dependency on computer programs for critical infrastructures, business processes andoperations. This boom is not abating, and is resulting in a corresponding increase in the number ofcompanies and individuals who join an increasing population of software engineers, enterprise applicationdevelopers and programmers. But regrettably, the boom has given rise to a host of ethical issues. Theability to make sound ethical judgement and decision is becoming very important as â€œhalf-bakedâ€ softwaredevelopers produce critical software that are supposed to run critical business functions and operations. Tocompound this problem the few technical schools or colleges that produce the very needed programmersand web designers do not have a clue that there is something negative creeping in from another angle;they do not have qualified or versed instructors to arm their graduates with the basic foundationknowledge in software professional ethics which is needed to effectively practise the art of softwareengineering in the society at large.This paper investigates the state of software engineering ethics in theface of Nigeriaâ€™s upwelling Information and Communications Technology and intention to produce and uselocally designed and implemented software. The paper calls attention to the nonchalance, dispassion andmass negligence attendant to this issue. It further highlights and calls for adherence to sound ethics at alllevels of software production in the Nigerian society at large. The paper uses a case-study and scenario toillustrate how to start doing so.